ECOTOURISM SITES IN SAMARKAND REGION AND THE ORGANIZATION OF SERVICES THERE (International Congress on Economics, Management and Business Studies, 2026)
Ecotourism sites in Samarkand Region lose competitiveness when reception, guiding, transport, and booking operate as disconnected functions instead of one guest-facing chain. To examine this service gap, a mixed-method case study combined a questionnaire, semi-structured interviews, and content analysis. Descriptive results showed the weakest point in booking convenience (2.10–4.60), while reception coordination was stronger (2.70–4.90) and perceived service quality stayed within 2.40–4.80. The regression model accounted for a substantial part of the variance (R² = 0.47). Coordination was the dominant predictor (β = 0.41, p
Keywords: sustainable tourism, stakeholder alignment, guest satisfaction, regional management, transport accessibility, service quality, Uzbekistan